2011
DOI: 10.1093/icesjms/fsr059
|View full text |Cite
|
Sign up to set email alerts
|

Possible effects of global warming on fish recruitment: shifts in spawning season and latitudinal distribution can alter growth of fish early life stages through changes in daylength

Abstract: Shoji, J., Toshito, S., Mizuno, K., and Kamimura, Y., Hori, M., Hirakawa, K. 2011. Possible effects of global warming on fish recruitment: shifts in spawning season and latitudinal distribution can alter growth of fish early life stages through changes in daylength. – ICES Journal of Marine Science, 68: 1165–1169. Changes in growth rates, shifts in the spawning season, and shifts in the spawning area (latitude) are expected after an increase in sea temperature resulting from global warming. Fish can avoid high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 13 publications
1
46
0
Order By: Relevance
“…Mean temperature from December to February in the Seto Inland Sea (11-18°C) is approximately 8°C higher than that in Sendai Bay (4-9°C: http://www.tnfri.fra.affrc.go.jp/). Recent analysis showed that the larval growth rate of S. cheni back-calculated by the use of otolith microstructure of January-extruded cohort was about 0.3 mm d -1 in the Seto Inland Sea and about 0.2 mm d -1 in Sendai Bay, and that there was a significant positive correlation between daily growth rates and ambient temperatures (Shoji et al 2011). The length-age relationships obtained during the larval and early juvenile periods were linear (Shoji et al 2011;present study).…”
Section: Occurrence Of Juvenile S Cheni In Vegetated Habitatsmentioning
confidence: 59%
See 1 more Smart Citation
“…Mean temperature from December to February in the Seto Inland Sea (11-18°C) is approximately 8°C higher than that in Sendai Bay (4-9°C: http://www.tnfri.fra.affrc.go.jp/). Recent analysis showed that the larval growth rate of S. cheni back-calculated by the use of otolith microstructure of January-extruded cohort was about 0.3 mm d -1 in the Seto Inland Sea and about 0.2 mm d -1 in Sendai Bay, and that there was a significant positive correlation between daily growth rates and ambient temperatures (Shoji et al 2011). The length-age relationships obtained during the larval and early juvenile periods were linear (Shoji et al 2011;present study).…”
Section: Occurrence Of Juvenile S Cheni In Vegetated Habitatsmentioning
confidence: 59%
“…Recent analysis showed that the larval growth rate of S. cheni back-calculated by the use of otolith microstructure of January-extruded cohort was about 0.3 mm d -1 in the Seto Inland Sea and about 0.2 mm d -1 in Sendai Bay, and that there was a significant positive correlation between daily growth rates and ambient temperatures (Shoji et al 2011). The length-age relationships obtained during the larval and early juvenile periods were linear (Shoji et al 2011;present study). Therefore, it is plausible that the differences in temperature would explain the difference in the seasonal timing of migration: the higher larval growth rate due to higher temperature would have resulted in the earlier migration (but at the same TL of 20 mm) of the S. cheni juveniles into the vegetated habitat in the Seto Inland Sea.…”
Section: Occurrence Of Juvenile S Cheni In Vegetated Habitatsmentioning
confidence: 59%
“…Differential phenological responses across species will lead to temporal mismatches among trophic levels (Visser and Both, 2005;Thackeray et al, 2010). Climate change will alter the seasonal and temporal extent of areas favorable to reproduction, growth and survival for marine species (e.g., Shoji et al, 2011). Species may respond directly to changes in temperature and other climatic variables and also indirectly through changes in food and habitat resources (Stewart et al, 2014;Sydeman et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Shifts in spring spawning phenology to earlier in the year cause there to be fewer hours of daylight available when visual predators are able to hunt, leading to depressed growth rates among larval fishes (Shoji et al, 2011). Shifts in spring spawning phenology to earlier in the year cause there to be fewer hours of daylight available when visual predators are able to hunt, leading to depressed growth rates among larval fishes (Shoji et al, 2011).…”
Section: Discussionmentioning
confidence: 99%